Sex and gender differences in myocarditis and dilated cardiomyopathy: An update - Fairweather, DeLisa; Beetler, Danielle J.; Musigk, Nicolas; Heidecker, Bettina; Lyle, Melissa A.; Cooper, Leslie T.; Bruno, Katelyn A. (Frontiers in Cardiovascular Medicine, 2023)
In the past decade there has been a growing interest in understanding sex and gender differences in myocarditis and dilated cardiomyopathy (DCM) and the purpose of this review is to provide an update on this topic including epidemiology, pathogenesis and clinical presentation, diagnosis and management Recently, many clinical studies have been conducted examining sex differences in myocarditis. Studies consistently report that myocarditis occurs more often in men than women with a sex ratio ranging from 1:2-4 female to male. Studies reveal that DCM also has a sex ratio of around 1:3 women to men and this is also true for familial/ genetic forms of DCM. Animal models have demonstrated that DCM develops after myocarditis in susceptible mouse strains and evidence exists for this progress clinically as well. A consistent finding is that myocarditis occurs primarily in men under 50 years of age, but in women after age 50 or post-menopause. In contrast, DCM typically occurs after age 50, although the age that post-myocarditis DCM occurs has not been investigated. In a small study, more men with myocarditis presented with symptoms of chest pain while women presented with dyspnea. Men with myocarditis have been found to have higher levels of heart failure biomarkers soluble ST2, creatine kinase, myoglobin and T helper 17-associated cytokines while women develop a better regulatory immune response. Studies of the pathogenesis of disease have found that Toll-like receptor (TLR)2 and TLR4 signaling pathways play a central role in increasing inflammation during myocarditis and in promoting remodeling and fibrosis that leads to DCM, and all of these pathways are elevated in males. Management of myocarditis follows heart failure guidelines and there are currently no disease-specific therapies. Research on standard heart failure medications reveal important sex differences. Overall, many advances in our understanding of the effect of biologic sex on myocarditis and DCM has occurred over the past decade, but many gaps in our understanding remain. A better understanding of sex and gender effects are needed to develop disease-targeted and individualized medicine approaches in the future.